SUPPORTING AND INHIBITING FACTORS FOR TEACHERS IN DEALING WITH DELINQUENT BEHAVIOR IN STUDENTS - Handayani, Nur; Saputra, Riyu; Berlian, Zainal; Mislawaty, Sri Eva; Purwandari, Elce (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to determine the supporting and inhibiting factors for teachers in dealing with students' delinquent behavior. The research location is Madrasah Aliyah Nurul Akhlak Biaro Baru. The method used in this research is qualitative. The research sample consisted of 6 people consisting of 1 school principal, 1 Guidance Counseling teacher, 1 Deputy Principal for Student Affairs, and 3 students. Data collection techniques consist of observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and the final step is drawing conclusions and verification. The results of the research stated that the supporting factors for the guidance and counseling teacher's strategy in overcoming delinquent behavior were that the principal and homeroom teacher supported the existence of counseling guidance activities, students with these activities experienced changes, little by little leaving behind the actions they experienced. Meanwhile, factors inhibiting guidance and counseling teachers from overcoming delinquent behavior include non-existent guidance and counseling rooms, inadequate guidance and counseling facilities, lack of time, and entrenched delinquent behavior.